2020
DOI: 10.1002/ehf2.12543
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of baroreflex activation therapy for heart failure with reduced ejection fraction: a rapid systematic review

Abstract: To retrieve and assess the available data in the literature about the safety and efficacy of baroreflex activation therapy (BAT) in heart failure with reduced ejection fraction (HFrEF) patients, through a rapid systematic review of clinical studies. Rapid systematic review of literature. Searched electronic databases included PubMed, EMBASE, CENTRAL, Scopus, and Web of Science using Mesh and free terms for heart failure and BAT. No language restriction was used for the searches. We included full peer reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This http://eduvest.greenvest.co.id result is consistent with the previous review. They revealed that BAT lower hospitalization rates and the number of days hospitalization after treatment (Schmidt et al, 2020). In other meta-analysis settings, there was no explanation about the hospitalization effect after BAT because they just explain its impact on reduced blood pressure among chronic heart failure patients (Wallbach et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This http://eduvest.greenvest.co.id result is consistent with the previous review. They revealed that BAT lower hospitalization rates and the number of days hospitalization after treatment (Schmidt et al, 2020). In other meta-analysis settings, there was no explanation about the hospitalization effect after BAT because they just explain its impact on reduced blood pressure among chronic heart failure patients (Wallbach et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with the previous review. They also found that Baroreflex Activation Therapy (BAT) effectively improve NYHA class and 6-MHWD among heart failure patients (Schmidt, Rodrigues, Schmidt, & Irigoyen, 2020). Furthermore, in other settings, a meta-analysis was performed to identified the correlation of Baroreflex Activation Therapy (BAT) and reduced of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Using the AMSTAR 2 system (Data S3), the systematic reviews were classed as low quality, 16 critically low quality [17][18][19][20] or moderate. 21 According to RoB2 (Data S4), the clinical trials had an uncertain 26 or high 24 risk of bias.…”
Section: Appraisal Of Methodological Quality and Bias Riskmentioning
confidence: 99%
“…The results of the systematic reviews [16][17][18][19][20][21] indicated that BAT is safe when performed by a well-trained multidisciplinary team. There were improvements in LVEF, NYHA class, quality of life, 6MWT, NT-proBNP levels, hospitalization rates and length of stay, and muscle sympathetic nerve activity.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Recently in Western countries, baroreflex activation therapy has been initiated in patients with heart failure to improve BRS, autonomic nervous system and cardiac functions as well as exercise tolerance 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%